Expatriate managers´ perception of whistleblowing in Czech environment - Simonyan, Lev (2020)
The cornerstone aim of the research was to obtain in-depth knowledge on the whistleblowing from the perspective of supervisors, and reveal potential areas of conflicts, which could lead to retaliation, non-disclosure of the wrongdoings, and frustration of the witnesses of unethical behavior as well as answering the following main research question: What is the attitude of foreign managers to phenomena of Whistleblowing in the context of Czech Republic? In order to fulfill the goal of the research, author selected to conduct semi-structured interviews with the selected participants from the expatriate supervisors in the context of Czech Republic. It was revealed that supervisors in the contemporary context of Czech Republic have very positive attitudes towards whistleblowing in general, finding it a good business practice improving the level of business conduct under certain circumstances such as: following the corporate guidance, reporting internally, and inclusion of the supervisor in the process. In addition to that, it was revealed that there is significance level of knowledge gap of supervisors with regards to the legal regulations of whistleblowing related activities, and their over-reliance on the corporate frameworks, which they perceived as single source of truth.